Kepemimpinan Kepala Madrasah Dalam Mengambil Keputusan - Ramdhan, Mohamad Azis; Suklani, Suklani (Perhimpunan Sarjana Ekonomi dan Bisnis, 2024)
The aim of this research is to formulate the leadership of Madrasah heads in decision making. This research method uses a qualitative approach. Data The collection techniques used are documentation studies and text studies in order to find information or data about the leadership of the madrasa head and decision making. That The collected data was analyzed using content analysis techniques and explained descriptively. The results of the research show that the leadership of the madrassah head as the person responsible for making policies in Islamic educational institutions plays a very important role in being able to determine whether the educational institution he leads will be successful or not in accordance with his strategy and leadership in making policies at the madrassah.